О стохастической модели статора турбогенератора - Остерник, Э. С. (НТУ "ХПИ", 2007)
The method for calculating the dynamics of the winding side of embedded stator is offered. This method is based on experiments over the materials of the winding bar and its model. Anisotropy of materials,in-plane shear, wave-like behavior of vibrations, and stochasticity of mechanical properties of materials are taken into consideration. Variational simulation takes into account the actual construction of bar fixing. It allows to evaluate the turbogenerator reliability in the process of operation.
Keywords: ремонт турбогенераторов; динамика статорных обмоток; магнитопривод; корпусная изоляция; модельный стержень; стержневая обмотка